1995
DOI: 10.1002/ceat.270180408
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer effects on kinetics of nonideal liquid phase ethyl tert‐butyl ether formation

Abstract: Ethyl tert-butyl ether (ETBE) is an alternative fuel oxygenate that can be produced in the liquid phase by addition of ethanol to isobutene catalyzed by sulfonic acid ion exchange resins. A generalized Langmuir-Hinshelwood rate expression is formulated in terms of the liquid phase activities of the reactants that is quasi-autocatalytic due to ethanol. This microkinetic model is combined with the generalized Maxwell-Stefan equations for a detailed investigation of the influence of multicomponent mass transfer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The global efficiency of the catalyst was mainly due to the process occurring on the macropores, since the efficiency in the gel microspheres is unity. The mass transfer effects on the kinetics of ETBE synthesis using Amberlyst 15 were modelled by Sundmacher et al (1995) and his collaborators considering the multicomponent mass transport in the liquid phase of macropores described by the generalized Maxwell-Stefan model, and the transport phenomena through the micropores and the surface diffusion on the gel microspheres were not taken into account explicitly; however, they were lumped in the tortuosity factor. The influence of catalyst particle diameter in the catalytic recovery of anthraquinones was studied in a batch reactor by Wärnå et al (2002).…”
Section: Sourcementioning
confidence: 99%
“…The global efficiency of the catalyst was mainly due to the process occurring on the macropores, since the efficiency in the gel microspheres is unity. The mass transfer effects on the kinetics of ETBE synthesis using Amberlyst 15 were modelled by Sundmacher et al (1995) and his collaborators considering the multicomponent mass transport in the liquid phase of macropores described by the generalized Maxwell-Stefan model, and the transport phenomena through the micropores and the surface diffusion on the gel microspheres were not taken into account explicitly; however, they were lumped in the tortuosity factor. The influence of catalyst particle diameter in the catalytic recovery of anthraquinones was studied in a batch reactor by Wärnå et al (2002).…”
Section: Sourcementioning
confidence: 99%
“…In the present reaction system, external mass transfer effects are avoided with stirring speeds of 750 rpm in the batch reactor, and flow rates of 0.031 g/s in the fixed-bed setup, as determined in previous works. 16,26,27 Internal mass transfer effects occur inside the catalyst. They become more noticeable at larger catalyst bead size and at higher reaction temperature.…”
Section: Resultsmentioning
confidence: 99%
“…MTBE and ETBE etherifications have been studied extensively throughout the years. [10][11][12][13][14][15][16] More recently, the production of propyl tert-butyl ether (PTBE), the next ether in the analogous series, obtained by addition of 1-propanol to isobutene, has also been investigated. 17 According to the literature, all these etherification reactions are reversible and exothermic, and the olefin-alcohol-ether mixtures behave strongly non-ideally.…”
Section: Introductionmentioning
confidence: 99%
“…For the acid catalyst reaction between iso-butene and methanol to form methyl tert-butyl ether, the traditional reactor followed by distillation concept has a complexity inherently because the mixture leaving the reactor forms three boiling azeotropes. (Sundmacher et al, 1995;Doherty and Buzad, 1992) The development and application of the equilibrium stage model for reactive distillation has been described in several types of research (Taylor et al, 1999;Jhon & Lee, 2002;Chen et al, 2003;Pyhalahti, 2005; Alfradique and Castier, 2005; Cheng and Yu, 2005;Katora et al,2005;Dalaouti and Seferlis, 2006;Venkateswarlu and Kumar, 2006;). The equilibrium stage models (Taylor et al, 1999) are demonstrated for calculates the material balances, vapor-liquid equilibrium equations, mole fraction summations and enthalpy balances (MESH).…”
Section: Introductionmentioning
confidence: 99%